Seagrass ecology and threats in the tropical Indo-Pacific bioregion - Richard Unsworth (Seagrass: Ecology, Uses and Threats, 2011)
Coles RG, Grech A, Rasheed, MA, McKenzie LJ, Unsworth RKF, Short F (2011) Seagrass ecology and threats in the tropical Indo-Pacific bioregion Chapter 9 In: Pirog RS (ed) (2011) Seagrass: Ecology, Uses and Threats Editors. 2010 Nova Science Publishers, Inc ISBN: 978-1-61761-987-8